Societal Security Trust Issues in Australia during the COVID-19 Pandemic in 2020 - Brudnicka-Żółtaniecka, Jowita (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
In late December 2019 and early January 2020 the first cases of a new coronavirus occurred in Wuhan. It is a virus characterised by similarities to SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome). On January 25, 2020 the initial case of infection by SARS-CoV-2 caused the disease COVID-19 in an Australian patient who later died from it. During my PhD thesis defence in September 2018 I would not have thought that one of the possible security scenarios which I designed for the South Pacific region, related to epidemic threats, would soon come true. Despite some obvious and high indicators resulting, for example, from a geopolitical location in the vicinity of China, the probability of an epidemic outbreak seemed nigh unbelievable. This article focuses on societal security. It is impossible to make a solid analysis of an epidemic impact on societal security in various countries in a single article; therefore, I concentrate specifically on the case of Australia. The goal of this article is to explain how Australians cope with the epidemic and if they are prepared for a drastic change in their lifestyles. Do they put trust in governmental institutions? What issues appear to be main societal threats in Australian society during the pandemic? I conclude with thoughts about new societal directions that are going to be implemented should the scale of the pandemic persist. Due to limited length, my overview is not exhaustive; instead, it focuses on core findings about the condition of Australian society during the pandemic.